Increasing Tourism Potential through Natural Resource Management and Development of Tourism Packages in Building Independence and Productivity of the Ngulungwetan Village Community - Alfian Fawzi; Duwi Rahmawati (Universitas STRADA Indonesia, 2024)
PPK ORMAWA is one of the MBKM activities held by the government to support student education so that it can be directly conveyed to the Indonesian people through students. The ORMAWA PPK activity is an activity that has 3 program aspects, one of which is Promotional Media, Services, and Tourism Village Product Requirements. Ngulungwetan Village is a tourist village where this village is also one of the villages where the average community has a low level of awareness of the potential of tourist villages. So with the tourist attraction of beach camping as a tourism village product in Ngulungwetan Village, now the community and pokdarwis (tourism awareness groups) can manage tourism well. Camping tourism uses Minister of Tourism and Creative Economy Regulation Number 7 of 2021, the KBLI group is included in the low-scale business category which must have a business permit in the form of a business registration number (NIB) (KEMENPAREKRAF, 2021). This service aims to increase the attractiveness of local and foreign tourists because there are tourist destinations in Ngulungwetan Village. The results obtained are that the ORMAWA PPK Team has created this program. With this program, it is hoped that it can increase the attractiveness of the community in Ngulungwetan Village in the world of tourism. So, with this program, it can improve the management of the tourist attraction of Kebo Beach, Ngulungwetan tourist village, especially beach camping as a superior product of the tourist village.